(untitled) (Revista Argentina de Musicología, 2021)
Tango was a central protagonist of the Argentine recording industry’s massification during the first half of the twentieth century. The 2000s witnessed a creative re-emergence of the genre under new production conditions. Since then, sound possibilities are broader, works have been progressively dematerialized, home studios have proliferated, and the DIY’s work logics have accentuated. Drawing on a multi-situated ethnography (2016-2021), I analyze the tango record’s current representation and the artistic decisions before, during, and after the recording. Through this exploration, I aim to answer three questions: what is hidden through the use of digital tools? Do they provoke significant musical contributions? And, what is the relationship between digital practices and labor flexibility?